(untitled) (Dermatology Reports, 2017)
The aim of this study was to determine the impact of melasma on quality of life (QoL) using the dermatology life quality index (DLQI) questionnaire in a group of outpatients. This study is questionnairebased. A total of 101 Turkish women suffering from melasma, who themselves were able to understand and complete the Turkish version of the DLQI questionnaire, were enrolled. This questionnaire included 10 questions; each of each was scored on a scale of 0-3, with a maximum score of 30. The data were analyzed after the results had been collated and the higher the DLQI score, the poorer the QoL. The participants’ mean age was 29.53±6.87 years, and mean DLQI score was 6.02±4.94. When we divided the participants into two subgroups according to age, the DLQI scores for younger and older individuals were 7.44±4.99 and 4.33±4.36, respectively (P=0.001). When the melasma area and severity index (MASI) score was used, participants with mild and moderate disease had mean DLQI scores of 5.80±4.72 and 7.11±5.90, respectively. No patient had severe disease. Melasma might affect the participants’ QoL, especially that of the younger individuals, in our study population.